Potential Novel Strategies for the Treatment of Dental Pulp-Derived Pain: Pharmacological Approaches and Beyond - Schuh, Christina M. A. P.; Benso, Bruna; Aguayo, Sebastian (Frontiers in Pharmacology, 2019)
The diagnosis and management of pain is an everyday occurrence in dentistry, and its effective control is essential to ensure the wellbeing of patients. Most tooth-associated pain originates from the dental pulp, a highly vascularized and innervated tissue, which is encased within mineralized dentin. It plays a crucial role in the sensing of stimuli from the local environment, such as infections (i.e. dental caries) and traumatic injury, leading to a local inflammatory response and subsequently to an increase in intra-pulp pressure, activating nerve endings. However, thermal, chemical and mechanical stimuli also have the ability to generate dental pulp pain, which presents mechanisms highly specific to this tissue and which have to be considered in pain management. Traditionally, the management of dental pulp pain has mostly been pharmacological, using non-steroidal anti-inflammatory drugs (NSAIDs) and opioids, or restorative (i.e. removal of dental caries), or a combination of both. Both research areas continuously present novel and creative approaches. This includes the modulation of thermo-sensitive transient receptor potential cation channels (TRPV) by newly designed drugs in pharmacological research, as well as the use of novel biomaterials, stem cells, exosomes and physical stimulation to obtain pulp regeneration in regenerative medicine. Therefore, the aim of this review is to present an up-to-date account of causes underlying dental pain, novel treatments involving the control of pain and inflammation and the induction of pulp regeneration, as well as insights in pain in dentistry from the physiological, pharmacological, regenerative and clinical perspectives.